Intermediate wheatgrass as a dual use crop for grain and grazing - Rusch, Hannah L.; Hunter, Mitchell C.; Kraus, Alan; Tautges, Nicole E.; Jungers, Jacob M. (Frontiers in Agronomy, 2025)
IntroductionIntermediate wheatgrass [Thinopyrum intermedium (Host) Barkworth & D.R. Dewey] (IWG) is a novel perennial grain crop with the potential for dual use (DU) in a system that includes the harvest of summer grain and straw as well as the grazing of crop regrowth. This could diversify grower income streams but impacts on productivity and profitability of DU systems need evaluation. MethodsA 4-year on-farm trial was conducted in Minnesota, USA comparing yields and net revenue of a grain+straw production system (GP) vs. a DU system. For both the GP and DU systems, the grain and straw yields from the summer harvest were evaluated, the subsequent IWG regrowth was measured in the fall and again in spring to quantify forage production and nutritive value, and the economic value of grain, straw, and forage were calculated. In the DU system, the herbage intake and forage utilization were also studied.Results and discussionThe GP system produced 42% more grain and 41% more straw than the DU system in year 2 but both systems produced similar grain and straw yields in year 3. The DU system produced greater grain yields than the GP in year 4. Across systems, the forage yield peaked in year 3. Both agronomic systems generally displayed similar forage yields of comparable nutritive value. Crude protein (CP) in fall and spring forage averaged 140 to 150 g kg-1 whereas CP was 30 g kg-1 in the summer straw, comparable to common annual small grains. The relative feed value of IWG forage in the fall was 100 and 127 in spring compared with 80 in the summer. The sale of higher year 2 grain yields in the GP system led to this system earning a net return to the enterprise of $721 ha-1 yr-1 with the DU system producing $609 ha-1 yr-1. In conclusion, grazing IWG can take advantage of on-farm forage resources to generate revenue but waiting to begin grazing until after the second-year grain harvest may reduce the risk of grain and straw yield losses to enhance net returns to the enterprise.